A cidadania digital em uma cidade inteligente: as interações digitais que transformam espaços analógicos com práticas cidadãs através do Instagram - Coelho, Vitor Daher (2023)
In this work, we seek to discuss how digital citizenship is exercised in a smart city within a social network. To this end, we began the debate by presenting the different perspectives on what would define a smart city and we argue that this concept is associated with the phenomenon of digital transformation, as innovation proposals in the management of municipal services are linked to the incorporation of new ICTs into everyday life. of cities. We present that there are different conceptions about smart cities, with a group of authors who highlight the importance of ICTs for improving the quality of life of citizens, who barely discuss socioeconomic aspects, the local context for the application of technology and the types of propositions. of governance while, on the other hand, proposals are made for an approach with a more holistic perspective, in which the focus of smart city analysis moves away from technology and towards human factors, such as the capabilities of citizens to appropriate proposed innovations. and governance models designed for greater participation of city residents in the decision-making process for allocating public resources. We discuss concepts related to citizenship and digital citizenship and used ethnomethodology as a theoretical-methodological reference for the empirical approach to the phenomenon of exercising digital citizenship within an Instagram page. Through qualitative research, we sought to understand how residents of Greater São Pedro exercise digital citizenship through the social network Instagram. We observed that, on numerous occasions, public figures and managers such as governor, mayor, secretaries of health, security, education, state deputies, councilors, executives from public transport companies, water supply companies and press professionals interact with followers of the page. in order to respond to the demands placed there. These interactions that begin in the digital environment, on numerous occasions, end up achieving the intended improvements in the public services provided there, which shows the connection between the digital and analogue spaces.